A oferta de moeda e sua relação com o crescimento econômico local - Romualdo Kohler (Universidade Regional do Noroeste do Estado do Rio Grande do Sul, 2004)
This work consists of the verification of the influence of currency, more specifically of the money offered in the economic growth of a small open and federated economy as it is the case in Brazils small and middle towns. Therefore, two basic hypotheses were emphasized: endogeny of currency in local economy in interaction with the income stream from and to abroad; and the domestic circulation unsteadiness rate of the currency. Trying to test these hypotheses, real events in a local model of the balance of payments were simulated, trying to verify the impact of the external relations on the internal monetary basis under laboratory conditions. The simulations corroborated a Keynesian hypothesis that currency affects the real part of economy, they confirmed also the endogeny of currency offer in the local economy in this specific case, and pointed to unsteadiness in the domestic circulation rate of the currency. In this regard, it can be defended that economic growth in a small open and federated economy depends of its domestic monetary liquidity. This liquidity depends basically on the economic performance of the basic sector, especially on export as currency source for its foreign relations and, secondly, on the development of the non-basic sector as one of the determinats of the circulation rate of currency.